From mobility to accessibility : transforming urban transportation and land-use planning - Levine, Jonathan (Jonathan C.); Grengs, Joe, 1962-; Merlin, Louis A., 1972- (Cornell University Press, 2019)
"This book argues for a shift in transportation and land-use planning away from their historic focus on mobility and toward accessibility as their primary measure of success"--